Biphenylnitrile-based self-assembled monolayers on Au(111): spectroscopic characterization and resonant excitation of the nitrile tail group - Ballav, Nirmalya; Schüpbach, Björn; Neppl, Stefan; Feulner, Peter; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2010)
A series of biphenylnitrile-based self-assembled monolayers (SAMs) on Au(111) was characterized by several complementary spectroscopic techniques, including resonant Auger electron spectroscopy (RAES). In spite of the disturbing role of nitrile, the SAMs exhibited high-quality and expected structural behavior, including the odd−even effects, even though with a lower extent than in the analogous nonsubstituted or methyl-substituted systems. A characteristic feature of the target films, and presumably also a general feature of oligophenyl-based SAMs, is a significant twist of the molecular backbone, similar to the situation in the analogous molecular crystals. No perceptible signal related to tail group-to-substrate transfer of the resonantly excited electron was recorded in the RAES spectra of the target films, even though such a transfer is energetically allowed in some of the cases. This was tentatively explained by the hypothesis that the charge transfer time is too long and lies beyond the range accessible by the core hole clock method via RAES in the present case. A characteristic feature of the RAES spectra of the target films at the excitation to the out-of plane orbital of the nitrile group is a strong suppression of the participator lines. This effect was qualitatively explained by the fact that the initial N1s core vacancy, the vacancy in the out-of-plane π1(C≡N*) orbital, and another valence vacancy participating in the decay are not localized on the same site in the case of this particular orbital and participator decay channels.